’n Geskiedenis van Afrikaans as kerktaal: van altaar tot kansel - Anastasia de Vries (Tydskrif vir Letterkunde, 2022)
This contribution shines a critical light on the representation of Afrikaans as a language of the Church in external histories about the development and advancement of the language, inclusive histories particularly. It seems the history of Afrikaans within a Christian or Church context has escaped the critical attention which since the 1970s created awareness of the politicisation of and silences in the history, and the way in which the history is documented. Therefore, the history of Afrikaans as a language of the Christian faith is still told from an exclusively white Reformed perspective and held as a 20 th century phenomenon, despite research pointing to its usage in the Moravian Church (Genadendal) in the 18 th century and the Anglican Church in the 19 th century. Though various denominations are included in so-called inclusive histories, it is done in a manner that suggests the dominance of the white Reformed Churches. These conclusions were primarily drawn from a content analysis of two inclusive histories, subjecting them to the same penetrating, sceptical questions of decades ago, focused primarily on the representation of Afrikaans as a language of the Church. For this purpose, the inclusive histories were analysed within the framework of poststructuralist tendencies which shifted the focus to historiography as a function of power, a meaning-making practice and history as a construct, not a reconstruction of the past. As such it creates space to imagine alternatives to the dominant discourse. To this end, the attention is drawn to the mobilisation of Afrikaans in the Roman Catholic Church since the 1820s as an alternative history of a spoken Afrikaans praying at the altar long before it was formalised and allowed to ascend the pulpit in the Reformed Churches since 1916.